Proof: “Any Statement Implies Itself”

Let p = any statement

“Any Statement Implies Itself”
written in logic:
(p => p)

Example: “I am Me.”

Prove: (p => p)
Proof :
(p => ((p => p) => p)) =>
((p => (p => p)) => (p => p))

p => ((p =>p) => p)

(p => (p => p)) => (p => p)

p => (p => p)

p => p [QED]

Advertisements

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s